Milk cathelicidin and somatic cell counts in dairy goats along the course of lactation. Issue 2 (3rd June 2019) - Tedde, Vittorio; Bronzo, Valerio; Puggioni, Giulia Maria Grazia; Pollera, Claudia; Casula, Antonio; Curone, Giulio; Moroni, Paolo; Uzzau, Sergio; Addis, Maria Filippa
Abstract: This research communication reports the evaluation of cathelicidin in dairy goat milk for its relationship with the somatic cell count (SCC) and microbial culture results. Considering the limited performances of SCC for mastitis monitoring in goats, there is interest in evaluating alternative diagnostic tools. Cathelicidin is an antimicrobial protein involved in innate immunity of the mammary gland. In this work, half-udder milk was sampled bimonthly from a herd of 37 Alpine goats along an entire lactation and tested with the cathelicidin ELISA together with SCC and bacterial culture. Cathelicidin and SCC showed a strong correlation ( r = 0.72; n = 360 milk samples). This was highest in mid-lactation ( r = 0.83) and lowest in late lactation ( r = 0.61), and was higher in primiparous (0.80, n = 130) than in multiparous goats (0.71, n = 230). Both markers increased with stage of lactation, but cathelicidin increased significantly less than SCC. In addition, peak level in late lactation was lower for cathelicidin (5.05-fold increase) than for SCC (7.64-fold increase). Twenty-one (5.8%) samples were positive to bacteriological culture, 20 for coagulase-negative staphylococci and one for Streptococcus spp.; 18 of them were positive to the cathelicidin ELISA (85.71% sensitivity). Sensitivity of SCC >500 000 and of SCC >1 000 000 cells/ml was lower (71.43 and 23.81%, respectively). Therefore, the high correlation of cathelicidin with SCC during the entire lactation, along with its lower increase in late lactation and good sensitivity in detecting intramammary infection (IMI), indicate a potential for monitoring subclinical mastitis in dairy goats. However, based on this preliminary assessment, specificity should be improved (40.41% for cathelicidin vs. 54.57 and 67.85% for SCC >500 000 and >1 000 000 cells/ml, respectively). Therefore, the application of cathelicidin for detecting goat IMI will require further investigation and optimization, especially concerning the definition of diagnostic thresholds.